Ensemble-based data assimilation for predictable zones and application for non-linear deep-water waves - Fujimoto, Wataru; Ishibashi, Kinya (Frontiers in Marine Science, 2023)
Data assimilation is a method to estimate unobserved physical state from a limited amount of data. Ensemble-based method is useful because it is easy to write a program code and to parallelize the code for faster computation. We propose an efficient ensemble-based method and tested it for water waves. The proposed method utilizes a rough estimate of how waves propagate. The proposed method is efficient than a previous method.